Hereditary ectodermal dysplasia: Report of 11 patients from a family - Seema Vaidya; Mukund Risbud; Avinash Kshar; Praveenkumar Ramdurg (Wolters Kluwer Medknow Publications, 2013)
Hereditary Ectodermal Dysplasia is an inherited disorder commonly involving skin, teeth, hair, and nails. We have observed ectodermal dysplasia (EDs) in 11 individuals over two generations in one family. Smooth, dry, thin skin was seen in most affected individuals. All had fine, slow-growing scalp hair and body hair and some had sparse eyebrows and short eyelashes. Nearly all showed decrease in sweating. Severe teeth abnormalities were seen in all patients and fingernail abnormalities were not so severe but toenail abnormalities were seen in all patients. No other abnormalities were seen in affected individuals in this family. It is very rare to find such a large family having ectodermal dysplasia.